Host spatiotemporal overlap in a park with high endemicity of Echinococcus multilocularis - Visscher, Darcy R.; Toews, Emilie; Pattison, Jesse; Walker, Philip D.; Kemna, Colborne; Musiani, Marco; Massolo, Alessandro (Frontiers in Parasitology, 2023)
There has been a spate of recent cases of human alveolar echinococcosis (AE) in Alberta, Canada. Alveolar echinococcosis is caused by Echinococcus multilocularis, which is prevalent among coyote populations and present in domestic dogs in Alberta. Using qPCR, we estimated the seasonal fecal prevalence of E. multilocularis in coyotes and dogs in a multiuse recreation area close to Edmonton, Alberta, where we also setup remote cameras to model seasonal changes in the overlap in temporal activity and the spatial intensity of use among coyotes, humans, and dogs, as a proxy of potential transmission. We detected E. multilocularis in 18 of 137 wild canid feces and none in 44 dog feces. After correcting for the qPCR test’s sensitivity and specificity, we estimated at 15.7% (9.7-22.7%, 95% CrI) the true fecal prevalence for coyotes. Temporal overlap between coyotes and both humans and dogs increased in the fall and winter relative to the spring and summer. Coyote intensity of use showed seasonal variations and was higher on maintained trails and locations closer to visitor parking and at sites with high intensity of dog use. Our results reinforce the need of an integrated approach, typical of both One-Health and Eco-Health, to park management for minimizing the likelihood of transmission where human and dog activity results in significant overlap with the one of the natural definitive hosts of zoonotic parasites.